VD_FINDINFO HC / 2016 / 1081 vom 24. November 2016 - VD Tribunal cantonal (2016)
MESURE PROVISIONNELLE, ACTION EN REVENDICATIONDROITS RÉELS, POSSESSION, NULLITÉ PARTIELLE | 641 al. 2 CC, 20 al. 2 CO, 261 al. 1 CPC (CH)